Konsep Dasar, Ruang Lingkup Psikologi Dewasa Dan Manula, Kondisi Dewasa Awal - Fauziah Nasution; Annisa Wibowo; Tania May Sabrina Nasution; Innayya Rahmadhini Edith (CV. ITTC INDONESIA, 2024)
Adult and elderly developmental psychology studies the physical, psychological and social changes that occur in individuals from early adulthood to old age. This research aims to identify the main factors that influence psychological and social development at various phases of adult life, analyze the challenges faced by individuals, and formulate intervention strategies to support their well-being. With a qualitative approach based on literature analysis, this research utilizes developmental theories such as Erikson, Santrock, and Goleman to understand individual psychosocial and emotional dynamics. The results show that fulfillment of developmental tasks, such as economic independence and social involvement, is positively correlated with psychological well-being. Conversely, failure to fulfill these duties increases the risk of psychological disorders, such as depression and anxiety. This research suggests the importance of community and policy-based interventions to improve the quality of life of individuals across different phases of adulthood.